A Case Study of Customer Experiences, Expectations and Satisfaction Level toward Services provided by E-Commerce Shopee during COVID-19 Pandemic in Malaysia - Khairul Anuar, Nur Izzati Binti; Zulkifli, Nur Shakirah Binti; Mohd Kassim, Nur Hidayah Binti; Zaihaimi, Nur Husnina Amila Binti; Kumar, Akash; Sinha, Akash; Yadav, Laxmi Suresh; Huei, Lok Yee; Jian, Oh Zi (AIBPM Publisher, 2022)
Shopee is an international company that focuses mainly on e-commerce. It is also known for being one of the globe's most significant and advanced online markets. Due to the pandemic outbreak, the company has boosted rapidly to serve consumers and sellers in different countries across America and Europe who wanted to make a purchase and sell their products online, with 343 million monthly visits. Shopee provides customers with a simple, fast, and delightful online shopping experience that millions worldwide enjoy daily. The study's objective is to examine the customer expectations, experiences and satisfaction levels toward using e-commerce Shopee during the COVID-19 pandemic in Malaysia. A total of 110 Shopee users from Malaysia participated in an online survey via a google form. Our findings provide new insights into customer expectations, experiences and satisfaction, which are helpful for the company. This study also provides recommendations that lead to improved customer satisfaction.Keywords: Shopee, E-Commerce, Expectations, Experiences, Customer Satisfaction, COVID-19, Malaysia